Examination the Influence of Grab Indonesia Social Media Marketing toward User Purchased Intention - Astika Ulfah Izzati; Frianka Anidea; Welan Mauli Angguna; Andriansyah Bari (Equity: Jurnal Ekonomi, 2023)
Nowadays social media has revolutionized as the media that facilitate interaction and information using User Generated Content (UGC). Due to this thing many people especially marketer utilize social media as marketing tool that is why people named it social media marketing. In term of marketing field social media is used to do branding activities, increase website traffic, increase customer and brand loyalty, enhance conversion rate, and create other activities for business exposure. Some researched found that utilizing social media marketing brings significant effect to increase purchased intention. That’s why authors want to know more about social media marketing especially in entertainment (ENT), interaction (INT), and customization (CUST) that happened on social media itself. This study will examine the effect of social media marketing of one of online platform named Grab Indonesia with Instagram account @grabid. The author examined and analyzed ENT, INT, and CUST in their social media especially Instagram toward customer’s purchased intention. ENT, INT, and CUST on @grabid social media could influence purchased intention (PI) both simultaneously and partially. Hopefully the result of this study could contribute in developing social media marketing literature, and become references for brands in developing social marketing strategy.